Xanthogranulomatous Pyelonephritis with Incomplete Double Ureter - Yutaro Hayashi; Takashi Kawahara; Yusuke Hattori; Kota Shimokihara; Sohgo Tsutsumi; Daiji Takamoto; Taku Mochizuki; Jun-ichi Teranishi; Yasushi Yumura; Yasuhide Miyoshi; Masako Otani; Hiroji Uemura (Case Reports in Medicine)
Introduction. Xanthogranulomatous pyelonephritis (XGP) is a type of chronic renal inflammation that usually occurs in immunocompromised middle-aged women with chronic urinary tract infection or ureteral obstruction induced by the formation of ureteral stones. XGP with an incomplete double ureter is extremely rare. Case Presentation. A 76-year-old woman was referred to our department to undergo further examination for a left renal tumor that was detected by ultrasonography. Dynamic contrast computed tomography (CT) revealed an enhanced tumor in the upper renal parenchyma. Laparoscopic radical nephrectomy was performed based on a preoperative diagnosis of renal cell carcinoma. Histological sections showed the aggregation of foam cells; thus, XGP was diagnosed. Conclusion. We herein report a rare case of XGP in the upper pole of the kidney, which might have been associated with an incomplete double ureter.